Conditioned place preference and spontaneous dorsal horn neuron activity in chronic constriction injury model in rats. Issue 12 (December 2015) - Dalm, Brian D.; Reddy, Chandan G.; Howard, Matthew A.; Kang, Sinyoung; Brennan, Timothy J.
Abstract : Abstract: Patients with neuropathic pain commonly present with spontaneous pain, in addition to allodynia and hyperalgesia. Although evoked responses in neuropathic pain models are well characterized, determining the presence of spontaneous pain is more challenging. We determined whether the chronic constriction injury (CCI) model could be used to measure effects of treatment of spontaneous pain, by evaluating dorsal horn neuron (DHN) spontaneous activity and spontaneous pain-related behaviors. We measured conditioned place preference (CPP) to analgesia produced by sciatic nerve block with bupivacaine in rats with established CCI. We undertook another CPP experiment using hind paw incision. We also examined DHN spontaneous activity in CCI rats. Although CCI produced nocifensive responses to mechanical stimuli, CPP to analgesic nerve block was not evident 14 days after injury: Compared with baseline (314 ± 65 seconds), CCI rats did not show a preference for the bupivacaine-paired chamber after conditioning (330 ± 102 seconds). However, sciatic nerve block after hind paw incision produced CPP on postoperative day 1, serving as a positive control. The proportion of spontaneously active DHNs (33%) was not significantly increased in CCI rats compared with the sham (21%). The median rate of spontaneous activity in the CCI group (12.6 impulses per second) was not different from the sham group (9.2 impulses per second). Also, there was no change in DHN spontaneous activity after sciatic nerve block with bupivacaine. Our findings suggest that CCI as a neuropathic pain model should not be used to measure effects of treatment of spontaneous pain driven by the peripheral input. Abstract : Spontaneous nociception, tested by conditioned place preference, and spontaneous dorsal horn neuron activity were not evident in the rat model of chronic constriction injury to the sciatic nerve.